Impact of peer dynamics and only-child experience on academic motivation among Chinese international graduate students in the U.S. - Wang, Chang; Mireles-Rios, Rebeca (Journal of International Students, 2025)
Chinese international graduate students (CIGs), growing up without siblings, under China’s One-Child policy, are particularly impacted by peer dynamics. This study explored the influence of peer dynamics and family structure on the academic motivation of CIGs in the U.S., using Bandura’s self-efficacy theory as a framework. A single-case study approach involved six in-depth interviews. Findings showed that CIGs, with high academic self-efficacy, favor limited and balanced peer interactions, forming deep connections with co-national peers while maintaining primarily academic interactions with host and other international peers. These diverse interactions affect academic motivation both positively and negatively, with personality traits playing a crucial role in shaping these peer interactions.